Single-agent carboplatin AUC10 in metastatic seminoma: A multi-centre UK study of 216 patients. (March 2022) - Alifrangis, Constantine; Sharma, Anand; Chowdhury, Shafi; Duncan, Sarah; Milic, Marina; Gogbashian, Andrew; Agarwal, Samita; Sahdev, Anju; Wilson, Peter; Harland, Stephen; Stoneham, Sara; Lockley, Michelle; et al.
Abstract: Background: Radiotherapy and cisplatin-based combination chemotherapy are accepted standard-of-care treatments for metastatic seminoma with excellent survival outcomes but with established short- and long-term morbidity. Carboplatin monotherapy may be a less toxic alternative; however early historic studies at AUC7 showed inferior outcomes. Objectives: To evaluate multi-institutional data on and toxicity and longer-term survival for metastatic seminoma patients treated with the single-agent carboplatin AUC10. Methods: We undertook a multi-institutional analysis incorporating all men with the International Germ Cell Cancer Collaborative Group good-prognosis metastatic seminoma treated until 2018. Carboplatin AUC10 was given every 21 days. Toxicity, progression-free survival (PFS), disease-specific survival (DSS) and overall survival were noted. Variables predictive of progression were identified. Results and limitations: 216 patients were treated. The three-year PFS rate was 96.5%, and five-year DSS was 98.3%. There were seven relapses, of which 5 were successfully salvaged with further chemotherapy ± surgery, and three non-seminoma–related deaths. There were no treatment-related deaths. Of 148/216 evaluable patients for toxicity, 37% and 27% suffered >/ = grade III neutropenia and thrombocytopenia, respectively. Twelve percent of patients needed a platelet or blood transfusion (or both). The incidence of febrile neutropenia was 5%. Conclusion: For metastatic seminoma, carboplatin AUC10 harbours a similar oncological efficacy to established therapies, with a low failure risk. The major acute toxicity was myelosuppression. Our study establishes carboplatin AUC10 as another standard-of-care treatment option for good-prognosis metastatic seminoma, with a potentially lower toxicity profile than other therapies. Highlights: Carboplatin AUC10 in metastatic seminoma shows 2-year progression-free survival rate of 96.5% and 3-year overall survival of 100%. It avoids cisplatin and bleomycin and is deliverable as an outpatient regimen. The rate of admission for neutropenic sepsis was low at 5%. Non-haematological toxicity including renal toxicity is low. The main toxicity was haematological with 12% of patients needing blood products.